A kind of anti-skid coating and its preparation method

By introducing materials such as Oklilin derivatives, premodified nano calcium carbonate and modified soybean oil into the resin-based anti-slip coating, an anti-slip floor with excellent anti-slip, flame retardant, anti-aging and self-repairing properties was prepared. Coating solves the problem that existing resin-based anti-slip coatings are prone to flammability.

CN118755387BActive Publication Date: 2025-02-11SUZHOU JIADIAN ANTI-SLIP PROTECTION TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411003256.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-25
Publication Date
2025-02-11
Estimated Expiration
2044-07-25

AI Technical Summary

Technical Problem

The existing resin-based anti-slip coating has the problem of low limit oxygen index and flammable, which leads to safety hazards in its use.

Method used

By reacting Oaklilin derivatives with premodified nano calcium carbonate and modified soybean oil and other materials, a floor anti-slip coating was prepared, which was performed in bisphenol A epoxy resin E-51 Curing molding.

Benefits of technology

The anti-slip floor coating not only has excellent anti-slip performance, but also has good flame retardant and anti-aging properties. Due to the presence of boric acid ester bonds, the coating has self-repairing properties, which significantly improves safety and service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure BDA0004962229360000031
    Figure BDA0004962229360000031
  • Figure BDA0004962229360000111
    Figure BDA0004962229360000111
Patent Text Reader

Abstract

The invention discloses a ground anti-skid coating and a preparation method thereof, and relates to the technical field of polymer materials. When preparing the ground anti-skid coating, the present invention reacts methyl cyanoacetate and 4,4'-diaminobenzophenone to obtain octocrylene derivatives; reacts nano calcium carbonate with γ-aminopropyltriethoxysilane to obtain pre-modified nano calcium carbonate; polycondenses octocrylene derivatives and 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide on pre-modified nano calcium carbonate to obtain modified nano calcium carbonate; reacts soybean oil with 3-mercapto-1,2-propylene glycol and 4-formylphenylboronic acid in sequence to obtain modified soybean oil; bisphenol A epoxy resin E-51, modified nano calcium carbonate, 4,4'-diaminodiphenylmethane, and modified soybean oil are uniformly mixed and solidified to obtain a ground anti-skid coating. The anti-skid floor coating prepared by the invention has excellent flame retardancy, anti-aging, anti-skid and self-repairing properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to an anti-slip floor coating and a preparation method thereof. Background Art

[0002] Anti-slip coating is a coating applied to the surface of the contacted object to form an anti-slip surface with a high friction coefficient. When in contact with it, the friction prevents people, vehicles or other objects from sliding, thus reducing the possibility of people slipping and falling or objects sliding. Anti-slip coating is often used on floors laid with tiles, marble or granite in hotels, schools, hospitals, nursing homes, swimming pools, etc. Among the many anti-slip treatment methods, it is an effective and convenient method that is applicable to almost all surfaces. It can also give the contacting surface a variety of effects, and even play a role in beautification, decoration and protection.

[0003] Resin-based anti-skid coatings are widely used in industrial and agricultural production, transportation, and national defense science and technology due to their low price and simple preparation process. The base resins used in common resin-based anti-skid coatings, such as epoxy resins and polyurethanes, have low limiting oxygen index and are easy to burn, which brings safety hazards to the use of the coatings. Therefore, the invention of a flame-retardant anti-skid coating for the ground has important practical significance and broad market prospects. Summary of the invention

[0004] The purpose of the present invention is to provide a ground anti-slip coating and a preparation method thereof to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention discloses an anti-skid floor coating. The anti-skid floor coating is prepared by polycondensing octocrylene derivatives and 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide on pre-modified nano-calcium carbonate to obtain modified nano-calcium carbonate; reacting pre-modified soybean oil with 4-formylphenylboronic acid to obtain modified soybean oil; and uniformly curing and molding bisphenol A epoxy resin E-51, modified nano-calcium carbonate, 4,4'-diaminodiphenylmethane and modified soybean oil.

[0007] As an optimization, the octocrylene derivative is prepared by reacting methyl cyanoacetate and 4,4'-diaminobenzophenone.

[0008] As an optimization, the pre-modified nano-calcium carbonate is prepared by reacting nano-calcium carbonate with γ-aminopropyltriethoxysilane.

[0009] As an optimization, the pre-modified soybean oil is prepared by reacting soybean oil with 3-mercapto-1,2-propanediol.

[0010] A method for preparing a floor anti-slip coating comprises the following steps:

[0011] (1) ammonium acetate and glacial acetic acid are mixed uniformly in a mass ratio of 1:(3-4) to prepare a catalyst solution; methyl cyanoacetate and 4,4'-diaminobenzophenone are added in a molar ratio of 1:1 to n-heptane with a mass of 10-12 times that of methyl cyanoacetate, stirred at 80-90°C and 300-500 r / min for 10-20 minutes, and the catalyst solution with a mass of 2-2.4 times that of methyl cyanoacetate is added dropwise at a uniform rate within 60 minutes, the temperature is raised to 98°C, stirred and refluxed for 6-7 hours, cooled to room temperature, and 0-2°C deionized water with a volume of 1.5-1.7 times that of n-heptane is added, mixed uniformly, allowed to stand for 3-4 hours, filtered, washed with deionized water for 3-5 times, and dried at 60-70°C under vacuum conditions for 6-8 hours to obtain an octocrylene derivative;

[0012] (2) Pre-modified nano-calcium carbonate, 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide, triethylamine, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:(2-3):(0.03-0.05):(10-12), and then an octocrylene derivative with a molar amount of 1.1-1.3 times that of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide is added, and the mixture is stirred at 55-65° C. and 300-500 r / min for 3-4 h under nitrogen protection, cooled to room temperature, filtered, washed with anhydrous ethanol and deionized water for 3-5 times respectively, and dried at 60-70° C. for 8-10 h under vacuum conditions to obtain modified nano-calcium carbonate;

[0013] (3) pre-modified soybean oil, 4-formylphenylboric acid, magnesium sulfate, and tetrahydrofuran are uniformly mixed in a mass ratio of 1:(2-3):(0.04-0.06):(8-10), stirred at 40-50° C. and 300-500 r / min for 8-10 h, and dried at 60-70° C. under vacuum conditions for 7-8 h to obtain modified soybean oil;

[0014] (4) Bisphenol A epoxy resin E-51, modified nano-calcium carbonate, 4,4'-diaminodiphenylmethane, and modified soybean oil are mixed evenly in a mass ratio of 1:(0.02-0.03):(0.2-0.3):(1.3-1.5), stirred at 10-30°C and 300-500 r / min for 20-30 min, poured into a polytetrafluoroethylene mold, kept at 90-100°C for 2-3 h, kept at 140-150°C for 1-2 h, cooled to room temperature, and then demolded to obtain an anti-slip floor coating.

[0015] As an optimization, the reaction process of the octocrylene derivative in step (1) is:

[0016]

[0017] As an optimization, the pre-modified nano-calcium carbonate in step (2) is prepared by uniformly mixing nano-calcium carbonate and anhydrous ethanol in a mass ratio of 1:(50-60), adding silane hydrolyzate in an amount of 8-10 times the mass of the nano-calcium carbonate, stirring at 50-60° C. and 300-500 r / min for 1-2 h, filtering, washing with anhydrous ethanol for 3-5 times, and drying at 50-60° C. under vacuum conditions for 7-8 h to obtain the pre-modified nano-calcium carbonate.

[0018] As an optimization, the silane hydrolyzate is prepared by mixing γ-aminopropyltriethoxysilane and deionized water in a mass ratio of 1:(20-30), adjusting the pH to 4-6 with a 1 mol / L oxalic acid aqueous solution, and stirring at 10-30°C and 300-500 r / min for 20-30 minutes to prepare the silane hydrolyzate.

[0019] As an optimization, the pre-modified soybean oil in step (3) is prepared by uniformly mixing soybean oil, 3-mercapto-1,2-propanediol, azobisisobutyronitrile, and N,N-dimethylformamide in a mass ratio of 1:(0.6-0.8):(0.03-0.05):(8-10), stirring at 70-80°C and 300-500r / min for 2-3h, and drying at 60-70°C under vacuum conditions for 7-8h to obtain the pre-modified soybean oil.

[0020] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0021] When preparing the anti-skid coating for the ground, the present invention comprises the following steps: reacting methyl cyanoacetate and 4,4'-diaminobenzophenone to obtain an octocrylene derivative; reacting nano calcium carbonate and gamma-aminopropyltriethoxysilane to obtain pre-modified nano calcium carbonate; polycondensing the octocrylene derivative and 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide on the pre-modified nano calcium carbonate to obtain modified nano calcium carbonate; reacting soybean oil with 3-mercapto-1,2-propylene glycol and 4-formylphenylboronic acid in sequence to obtain modified soybean oil; and uniformly mixing bisphenol A epoxy resin E-51, modified nano calcium carbonate, 4,4'-diaminodiphenylmethane and modified soybean oil to form a solidified anti-skid coating for the ground.

[0022] Firstly, methyl cyanoacetate and 4,4'-diaminobenzophenone are reacted to obtain octocrylene derivatives; nano calcium carbonate is reacted with γ-aminopropyltriethoxysilane to obtain pre-modified nano calcium carbonate, and amino groups are introduced into the pre-modified nano calcium carbonate; the diamino groups on the octocrylene derivatives react with the phosphochlorine on 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide, and polycondense and grow on the pre-modified nano calcium carbonate to obtain modified nano calcium carbonate, and octocrylene structure and phosphorus element are introduced into the modified nano calcium carbonate; the introduction of phosphorus element can give the anti-slip coating on the ground excellent flame retardant properties; octocrylene belongs to the cinnamic acid compound, and due to the conjugated effect between the benzene ring and the carbonyl group in this type of compound, it can effectively absorb medium-wave ultraviolet rays, and give the anti-slip coating on the ground excellent anti-aging properties.

[0023] Secondly, the carbon-carbon double bond on the soybean oil molecular chain is reacted with the thiol group on 3-mercapto-1,2-propylene glycol to obtain pre-modified soybean oil, and the 1,2-propylene glycol on the pre-modified soybean oil is reacted with 4-formylphenylboronic acid to obtain modified soybean oil, and borate ester bonds and aldehyde groups are introduced into the modified soybean oil; the modified soybean oil is added to the epoxy resin as a diluent, and the aldehyde group on the modified soybean oil can react with 4,4'-diaminodiphenylmethane to participate in the curing of the epoxy resin. The borate ester bond is a dynamic covalent bond that can undergo ester exchange at room temperature to give the floor an anti-slip coating. The method comprises the following steps: first, mixing bisphenol A epoxy resin E-51, modified nano calcium carbonate, 4,4'-diaminodiphenylmethane and modified soybean oil and uniformly curing and forming the anti-skid coating for the floor; nano calcium carbonate is an inorganic functional chemical filler. Adding nano calcium carbonate as anti-skid granular material to resin can increase the friction coefficient of the resin. However, nano calcium carbonate has poor compatibility with resin and is easy to agglomerate, and thus cannot achieve an excellent anti-skid effect. Surface modification can make nano calcium carbonate evenly dispersed in the matrix resin, which can give the anti-skid coating for the floor excellent anti-skid performance. DETAILED DESCRIPTION

[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0025] Example 1

[0026] A method for preparing a floor anti-slip coating, the method comprising the following steps:

[0027] (1) ammonium acetate and glacial acetic acid are mixed in a mass ratio of 1:3 to prepare a catalyst solution; methyl cyanoacetate and 4,4'-diaminobenzophenone are added in a molar ratio of 1:1 to n-heptane with a mass of 10 times that of methyl cyanoacetate, stirred at 80°C and 300 r / min for 20 minutes, and the catalyst solution with a mass of 2 times that of methyl cyanoacetate is added dropwise at a uniform rate within 60 minutes, the temperature is raised to 98°C, stirred and refluxed for 6 hours, cooled to room temperature, 0°C deionized water with a volume of 1.5 times that of n-heptane is added, mixed evenly, allowed to stand for 3 hours, filtered, washed with deionized water 3 times, and dried at 60°C under vacuum conditions for 8 hours to obtain an octocrylene derivative;

[0028] (2) γ-aminopropyltriethoxysilane and deionized water were mixed at a mass ratio of 1:20, the pH was adjusted to 4 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 10°C and 300 r / min for 30 min to prepare a silane hydrolyzate; nano-calcium carbonate and anhydrous ethanol were mixed at a mass ratio of 1:50, 8 times the mass of the nano-calcium carbonate was added to the silane hydrolyzate, and the mixture was stirred at 50°C and 300 r / min for 2 h, filtered, washed with anhydrous ethanol for 3 times, and dried at 50°C under vacuum for 8 h to prepare a pre-modified nano-calcium carbonate; the pre-modified nano-calcium carbonate, 3,9-dichloro-2,4,8, 10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide, triethylamine and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:2:0.03:10, and then 1.1 times the molar amount of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide was added into an octocrylene derivative, and the mixture was stirred at 55°C and 300 r / min for 4 hours under nitrogen protection, cooled to room temperature, filtered, washed with anhydrous ethanol and deionized water for 3 times respectively, and dried at 60°C for 10 hours under vacuum conditions to obtain modified nano calcium carbonate;

[0029] (3) Soybean oil, 3-mercapto-1,2-propanediol, azobisisobutyronitrile, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.6:0.03:8, stirred at 70°C and 300 r / min for 3 h, and dried at 60°C for 8 h under vacuum conditions to obtain pre-modified soybean oil; pre-modified soybean oil, 4-formylphenylboric acid, magnesium sulfate, and tetrahydrofuran were mixed uniformly in a mass ratio of 1:2:0.04:8, stirred at 40°C and 300 r / min for 10 h, and dried at 60°C for 8 h under vacuum conditions to obtain modified soybean oil;

[0030] (4) Bisphenol A epoxy resin E-51, modified nano-calcium carbonate, 4,4'-diaminodiphenylmethane, and modified soybean oil were mixed evenly in a mass ratio of 1:0.02:0.2:1.3, stirred at 10°C and 300 r / min for 30 min, poured into a polytetrafluoroethylene mold, kept at 90°C for 3 h, kept at 140°C for 2 h, cooled to room temperature, and demolded to obtain an anti-slip floor coating.

[0031] Example 2

[0032] A method for preparing a floor anti-slip coating, the method comprising the following steps:

[0033] (1) ammonium acetate and glacial acetic acid are mixed uniformly at a mass ratio of 1:3.5 to prepare a catalyst solution; methyl cyanoacetate and 4,4'-diaminobenzophenone are added in a molar ratio of 1:1 to n-heptane with a mass ratio of 11 times that of methyl cyanoacetate, stirred at 85°C and 400 r / min for 15 minutes, and the catalyst solution with a mass ratio of 2.2 times that of methyl cyanoacetate is added dropwise at a uniform rate within 60 minutes, the temperature is raised to 98°C, stirred and refluxed for 6.5 hours, cooled to room temperature, 1.6 times the volume of n-heptane with a temperature of 1°C deionized water is added, mixed uniformly, allowed to stand for 3.5 hours, filtered, washed with deionized water 4 times, and dried at 65°C under vacuum conditions for 7 hours to obtain an octocrylene derivative;

[0034] (2) γ-aminopropyltriethoxysilane and deionized water were mixed at a mass ratio of 1:25, the pH was adjusted to 5 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 20°C and 400 r / min for 25 min to prepare a silane hydrolyzate; nano-calcium carbonate and anhydrous ethanol were mixed at a mass ratio of 1:55, 9 times the mass of the nano-calcium carbonate was added to the silane hydrolyzate, and the mixture was stirred at 55°C and 400 r / min for 1.5 h, filtered, washed with anhydrous ethanol for 4 times, and dried at 55°C under vacuum for 7.5 h to prepare a pre-modified nano-calcium carbonate; the pre-modified nano-calcium carbonate and 3,9-dichloro-2,4,8, 10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide, triethylamine and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:2.5:0.04:11, and then an octocrylene derivative with a molar amount of 1.2 times that of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide was added, and the mixture was stirred at 60°C and 400r / min for 3.5h under nitrogen protection, cooled to room temperature, filtered, washed with anhydrous ethanol and deionized water 4 times respectively, and dried at 65°C for 9h under vacuum conditions to obtain modified nano calcium carbonate;

[0035] (3) Mix soybean oil, 3-mercapto-1,2-propanediol, azobisisobutyronitrile, and N,N-dimethylformamide in a mass ratio of 1:0.7:0.04:9, stir and react at 75°C and 400 r / min for 2.5 hours, and dry at 65°C for 7.5 hours under vacuum conditions to obtain pre-modified soybean oil; mix pre-modified soybean oil, 4-formylphenylboric acid, magnesium sulfate, and tetrahydrofuran in a mass ratio of 1:2.5:0.05:9, stir and react at 45°C and 400 r / min for 9 hours, and dry at 65°C for 7.5 hours under vacuum conditions to obtain modified soybean oil;

[0036] (4) Bisphenol A epoxy resin E-51, modified nano-calcium carbonate, 4,4'-diaminodiphenylmethane, and modified soybean oil were mixed evenly in a mass ratio of 1:0.025:0.25:1.4, stirred at 20°C and 400 r / min for 25 min, poured into a polytetrafluoroethylene mold, kept at 95°C for 2.5 h, kept at 145°C for 1.5 h, cooled to room temperature, and then demolded to obtain an anti-slip floor coating.

[0037] Example 3

[0038] A method for preparing a floor anti-slip coating, the method comprising the following steps:

[0039] (1) ammonium acetate and glacial acetic acid are mixed uniformly in a mass ratio of 1:4 to prepare a catalyst solution; methyl cyanoacetate and 4,4'-diaminobenzophenone are added in a molar ratio of 1:1 to n-heptane with a mass of 12 times that of methyl cyanoacetate, stirred at 90°C and 500 r / min for 10 minutes, and the catalyst solution with a mass of 2.4 times that of methyl cyanoacetate is added dropwise at a uniform rate within 60 minutes, the temperature is raised to 98°C, stirred and refluxed for 7 hours, cooled to room temperature, and 2°C deionized water with a volume of 1.7 times that of n-heptane is added, mixed uniformly, allowed to stand for 4 hours, filtered, washed with deionized water 5 times, and dried at 70°C under vacuum conditions for 6 hours to obtain an octocrylene derivative;

[0040] (2) γ-aminopropyltriethoxysilane and deionized water were mixed at a mass ratio of 1:30, the pH was adjusted to 6 with a 1 mol / L oxalic acid aqueous solution, and the mixture was stirred at 30°C and 500 r / min for 20 min to prepare a silane hydrolyzate; nano-calcium carbonate and anhydrous ethanol were mixed at a mass ratio of 1:60, 10 times the mass of the nano-calcium carbonate silane hydrolyzate was added, and the mixture was stirred at 60°C and 500 r / min for 1 h, filtered, washed with anhydrous ethanol for 5 times, and dried at 60°C under vacuum for 7 h to prepare a pre-modified nano-calcium carbonate; the pre-modified nano-calcium carbonate and 3,9-dichloro-2,4,8 ,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide, triethylamine, and N,N-dimethylformamide are mixed uniformly in a mass ratio of 1:3:0.05:12, and then octocrylene derivatives with a molar amount of 1.3 times that of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide are added, and the mixture is stirred at 65°C and 500r / min for 3h under nitrogen protection, cooled to room temperature, filtered, washed with anhydrous ethanol and deionized water for 5 times respectively, and dried at 70°C for 8h under vacuum conditions to obtain modified nano calcium carbonate;

[0041] (3) Soybean oil, 3-mercapto-1,2-propanediol, azobisisobutyronitrile, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:0.8:0.05:10, stirred at 80°C and 500 r / min for 2 h, and dried at 70°C for 7 h under vacuum conditions to obtain pre-modified soybean oil; pre-modified soybean oil, 4-formylphenylboric acid, magnesium sulfate, and tetrahydrofuran were mixed uniformly in a mass ratio of 1:3:0.06:10, stirred at 50°C and 500 r / min for 8 h, and dried at 70°C for 7 h under vacuum conditions to obtain modified soybean oil;

[0042] (4) Bisphenol A epoxy resin E-51, modified nano-calcium carbonate, 4,4'-diaminodiphenylmethane, and modified soybean oil were mixed evenly in a mass ratio of 1:0.03:0.3:1.5, stirred at 30°C and 500 r / min for 20 min, poured into a polytetrafluoroethylene mold, kept at 100°C for 2 h, kept at 150°C for 1 h, cooled to room temperature, and then demolded to obtain an anti-slip coating for the floor.

[0043] Comparative Example 1

[0044] The preparation method of the anti-slip coating on the floor of Comparative Example 1 is different from that of Example 2 in that step (1) is not performed, and step (2) is modified as follows: γ-aminopropyltriethoxysilane and deionized water are mixed in a mass ratio of 1:25, the pH is adjusted to 5 with a 1 mol / L oxalic acid aqueous solution, and stirred at 20°C and 400 r / min for 25 min to prepare a silane hydrolyzate; nano-calcium carbonate and anhydrous ethanol are mixed in a mass ratio of 1:55, silane hydrolyzate with a mass of 9 times that of the nano-calcium carbonate is added, and the reaction is stirred at 55°C and 400 r / min for 1.5 h, filtered, washed with anhydrous ethanol 4 times, and dried at 55°C under vacuum for 7.5 h to obtain pre-modified nano-calcium carbonate; the pre- Modified nano-calcium carbonate, 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide, triethylamine, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:2.5:0.04:11, and then 1,4-butanediamine with a molar amount of 1.2 times that of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide was added, and the mixture was stirred at 60° C. and 400 r / min for 3.5 h under nitrogen protection, cooled to room temperature, filtered, washed with anhydrous ethanol and deionized water 4 times each, and dried at 65° C. for 9 h under vacuum conditions to obtain modified nano-calcium carbonate. The remaining steps were the same as those in Example 2.

[0045] Comparative Example 2

[0046] The difference between the preparation method of the anti-slip coating on the ground in Comparative Example 2 and that in Example 2 is that step (2) is different. Step (2) is modified as follows: γ-aminopropyltriethoxysilane and deionized water are mixed uniformly in a mass ratio of 1:25, the pH is adjusted to 5 with a 1 mol / L oxalic acid aqueous solution, and stirred at 20°C and 400 r / min for 25 min to prepare a silane hydrolyzate; nano calcium carbonate and anhydrous ethanol are mixed uniformly in a mass ratio of 1:55, silane hydrolyzate with 9 times the mass of nano calcium carbonate is added, the reaction is stirred at 55°C and 400 r / min for 1.5 h, filtered, and washed with anhydrous ethanol. Wash with ethanol 4 times, dry at 55°C for 7.5h under vacuum conditions to obtain pre-modified nano calcium carbonate; mix pre-modified nano calcium carbonate, 1,4-dichlorobutane, triethylamine, and N,N-dimethylformamide in a mass ratio of 1:2.5:0.04:11, add octocrylene derivatives with a molar amount of 1.2 times that of 1,4-dichlorobutane, stir and react at 60°C and 400r / min for 3.5h under nitrogen protection, cool to room temperature, filter, wash with anhydrous ethanol and deionized water 4 times each, dry at 65°C for 9h under vacuum conditions to obtain modified nano calcium carbonate. The remaining steps are the same as in Example 2.

[0047] Comparative Example 3

[0048] The preparation method of the anti-skid coating for the floor in Comparative Example 3 is different from that in Example 2 in that step (3) is not performed, and step (4) is modified as follows: bisphenol A epoxy resin E-51, modified nano calcium carbonate, 4,4'-diaminodiphenylmethane, and soybean oil are uniformly mixed in a mass ratio of 1:0.025:0.25:1.4, stirred at 20°C and 400 r / min for 25 min, poured into a polytetrafluoroethylene mold, kept at 95°C for 2.5 h, kept at 145°C for 1.5 h, cooled to room temperature, and then demolded to obtain the anti-skid coating for the floor. The remaining steps are the same as those in Example 2.

[0049] Comparative Example 4

[0050] The preparation method of the anti-skid coating for floor in Comparative Example 4 is different from that in Example 2 in that step (1) and step (2) are not performed, and step (4) is modified as follows: bisphenol A epoxy resin E-51, nano calcium carbonate, 4,4'-diaminodiphenylmethane, and modified soybean oil are uniformly mixed in a mass ratio of 1:0.025:0.25:1.4, stirred at 20°C and 400 r / min for 25 min, poured into a polytetrafluoroethylene mold, kept at 95°C for 2.5 h, kept at 145°C for 1.5 h, cooled to room temperature, and then demoulded to obtain the anti-skid coating for floor. The remaining steps are the same as those in Example 2.

[0051] Test Example 1

[0052] Flame retardant performance test

[0053] Test method: The examples and comparative examples were prepared into standard specimens according to GB / T5454, and the limiting oxygen index of the standard specimens was tested. The results are shown in Table 1.

[0054] Table 1

[0055] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 28.56 Comparative Example 1 28.19 Example 2 29.13 Comparative Example 2 21.42 Example 3 28.79 Comparative Example 3 28.26 Comparative Example 4 19.96

[0056] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the anti-slip floor coating prepared by the present invention has good flame retardant properties.

[0057] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Examples 2 and 4, indicating that pre-modified nano-calcium carbonate is prepared by reacting nano-calcium carbonate with γ-aminopropyltriethoxysilane, and amino groups are introduced into the pre-modified nano-calcium carbonate; the diamino group on the octocrylene derivative reacts with the phosphochlorine on 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide, and polycondenses on the pre-modified nano-calcium carbonate to prepare modified nano-calcium carbonate, and phosphorus element is introduced into the modified nano-calcium carbonate; the introduction of phosphorus element can give the floor anti-slip coating excellent flame retardant properties.

[0058] Test Example 2

[0059] Anti-slip performance test

[0060] Test method: The static friction coefficients of the examples and comparative examples were tested according to GB / T 9263 "Determination of the anti-slip properties of anti-slip coatings". The results are shown in Table 2.

[0061] Table 2

[0062] Static friction coefficient Static friction coefficient Example 1 0.867 Comparative Example 1 0.861 Example 2 0.881 Comparative Example 2 0.857 Example 3 0.879 Comparative Example 3 0.863 Comparative Example 4 0.521

[0063] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the anti-slip coating for the floor prepared by the present invention has good anti-slip performance.

[0064] By comparison, the static friction coefficients of Examples 1 to 3 are greater than that of Comparative Example 4, indicating that methyl cyanoacetate and 4,4'-diaminobenzophenone are reacted to obtain octocrylene derivatives; nano-calcium carbonate is reacted with γ-aminopropyltriethoxysilane to obtain pre-modified nano-calcium carbonate, and amino groups are introduced into the pre-modified nano-calcium carbonate; the diamino groups on the octocrylene derivatives react with the phosphinothiolate on 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide to form polycondensed growth on the pre-modified nano-calcium carbonate. Modified nano calcium carbonate is obtained; bisphenol A epoxy resin E-51, modified nano calcium carbonate, 4,4'-diaminodiphenylmethane and modified soybean oil are uniformly mixed and solidified to obtain a floor anti-skid coating; nano calcium carbonate is an inorganic functional chemical filler, and adding nano calcium carbonate as anti-skid granular material to resin can improve the friction coefficient of the resin, but nano calcium carbonate has poor compatibility with resin and is easy to agglomerate, and cannot achieve an excellent anti-skid effect. Through surface modification, nano calcium carbonate can be uniformly dispersed in the matrix resin, which can give the floor anti-skid coating excellent anti-skid performance.

[0065] Test Example 3

[0066] Anti-aging performance test

[0067] Test method: The tensile strength of the embodiment and the comparative example was tested on an electronic universal testing machine according to GB / T1040.3, and then the unstretched original sample was irradiated with a xenon arc lamp for 72 hours. The tensile strength of the embodiment and the comparative example after ultraviolet aging treatment was tested on an electronic universal testing machine according to GB / T1040.3, and the change rate of the tensile strength of the embodiment and the comparative example before and after ultraviolet aging treatment was calculated, tensile strength change rate = (original tensile strength of the sample - tensile strength of the sample after ultraviolet aging treatment / original tensile strength of the sample) × 100%. The results are shown in Table 3

[0068] Table 3

[0069]

[0070] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the anti-slip coating for the floor prepared by the present invention has good anti-aging performance.

[0071] By comparison, the change rates of tensile strength of Examples 1 to 3 are smaller than those of Comparative Examples 1 and 4, indicating that octocrylene derivatives are prepared by reacting methyl cyanoacetate and 4,4'-diaminobenzophenone; pre-modified nano-calcium carbonate is prepared by reacting nano-calcium carbonate with γ-aminopropyltriethoxysilane, and amino groups are introduced into the pre-modified nano-calcium carbonate; the diamino groups on the octocrylene derivative react with the phosphochlorine on 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide, and grow by polycondensation on the pre-modified nano-calcium carbonate to prepare modified nano-calcium carbonate, and octocrylene structure is introduced into the modified nano-calcium carbonate; octocrylene belongs to the cinnamic acid compound, and due to the conjugated effect of the benzene ring and the carbonyl group in this type of compound, it can effectively absorb medium-wave ultraviolet rays, giving the anti-slip coating on the ground excellent anti-aging properties.

[0072] Test Example 4

[0073] Self-healing performance test

[0074] Test method: The tensile strength of the embodiment and the comparative example was tested on an electronic universal testing machine according to GB / T1040.3, and then a notch of 3 cm in length and 0.5 cm in depth was cut on the unstretched original spline, and the spline was left standing at 60°C for 10 hours, cooled to room temperature and then left standing for another 10 hours to obtain the self-repaired spline. The tensile strength of the embodiment and the comparative example after self-repair was tested on an electronic universal testing machine according to GB / T1040.3, and the self-repair rate of the embodiment and the comparative example was calculated, and the self-repair rate = (tensile strength of the spline after self-repair / original tensile strength of the spline) × 100%. The results are shown in Table 4.

[0075] Table 4

[0076] Self-repair rate (%) Self-repair rate (%) Example 1 96.22 Comparative Example 1 95.89 Example 2 97.28 Comparative Example 2 96.08 Example 3 96.45 Comparative Example 3 62.17 Comparative Example 4 95.97

[0077] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 4, it can be found that the anti-slip coating prepared by the present invention has good self-repairing performance.

[0078] By comparison, the self-repairing rates of Examples 1 to 3 are greater than that of Comparative Example 3, indicating that the carbon-carbon double bond on the soybean oil molecular chain undergoes an addition reaction with the thiol group on 3-thiol-1,2-propylene glycol to obtain pre-modified soybean oil, the 1,2-propylene glycol on the pre-modified soybean oil reacts with 4-formylphenylboronic acid to obtain modified soybean oil, and a borate ester bond and an aldehyde group are introduced into the modified soybean oil; the modified soybean oil is added to the epoxy resin as a diluent, the aldehyde group on the modified soybean oil can react with 4,4'-diaminodiphenylmethane to participate in the curing of the epoxy resin, and the borate ester bond is a dynamic covalent bond that can undergo ester exchange at room temperature, thereby giving the floor anti-slip coating excellent self-repairing properties.

[0079] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A non-slip floor coating, characterized in that: The anti-slip floor coating is prepared by polycondensing octocrylene derivatives and 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide on pre-modified nano-calcium carbonate to obtain modified nano-calcium carbonate; reacting pre-modified soybean oil with 4-formylphenylboronic acid to obtain modified soybean oil; and uniformly curing and molding bisphenol A epoxy resin E-51, modified nano-calcium carbonate, 4,4'-diaminodiphenylmethane, and modified soybean oil. The octocrylene derivative is prepared by reacting methyl cyanoacetate and 4,4'-diaminobenzophenone; The pre-modified soybean oil is prepared by reacting soybean oil with 3-mercapto-1,2-propylene glycol.

2. The anti-slip coating according to claim 1, characterized in that: The pre-modified nano calcium carbonate is prepared by reacting nano calcium carbonate with gamma-aminopropyltriethoxysilane.

3. A method for preparing a non-slip floor coating, characterized in that: The method comprises the following preparation steps: (1) ammonium acetate and glacial acetic acid are mixed evenly in a mass ratio of 1:(3-4) to prepare a catalyst solution; methyl cyanoacetate and 4,4'-diaminobenzophenone are added in a molar ratio of 1:1 to n-heptane with a mass of 10-12 times that of methyl cyanoacetate, stirred at 80-90°C and 300-500 r / min for 10-20 min, and the catalyst solution with a mass of 2-2.4 times that of methyl cyanoacetate is added dropwise at a uniform rate within 60 min, the temperature is raised to 98°C and stirred under reflux for 6-7 h, cooled to room temperature, and 0-2°C deionized water with a volume of 1.5-1.7 times that of n-heptane is added, the mixture is mixed evenly, allowed to stand for 3-4 h, filtered, washed with deionized water for 3-5 times, and dried at 60-70°C under vacuum conditions for 6-8 h to obtain an octocrylene derivative; (2) Pre-modified nano-calcium carbonate, 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide, triethylamine, and N,N-dimethylformamide were mixed uniformly in a mass ratio of 1:(2-3):(0.03-0.05):(10-12), and then an octocrylene derivative with a molar amount of 1.1-1.3 times that of 3,9-dichloro-2,4,8,10-tetraoxa-3,9-diphosphaspiro[5.5]undecane-3,9-dioxide was added, and the mixture was stirred at 55-65°C and 300-500 r / min for 3-4 hours under nitrogen protection, cooled to room temperature, filtered, washed with anhydrous ethanol and deionized water for 3-5 times respectively, and dried at 60-70°C under vacuum conditions for 8-10 hours to obtain modified nano-calcium carbonate; (3) Pre-modified soybean oil, 4-formylphenylboric acid, magnesium sulfate and tetrahydrofuran were mixed uniformly in a mass ratio of 1:(2-3):(0.04-0.06):(8-10), stirred at 40-50°C and 300-500 r / min for 8-10 h, and dried at 60-70°C under vacuum conditions for 7-8 h to obtain modified soybean oil; (4) Mix bisphenol A epoxy resin E-51, modified nano-calcium carbonate, 4,4'-diaminodiphenylmethane and modified soybean oil in a mass ratio of 1:(0.02~0.03):(0.2~0.3):(1.3~1.5), stir at 10~30℃ and 300~500r / min for 20~30min, pour into a polytetrafluoroethylene mold, keep warm at 90~100℃ for 2~3h, keep warm at 140~150℃ for 1~2h, cool to room temperature and demold to obtain an anti-slip coating for the floor.

4. The method for preparing a non-slip floor coating according to claim 3, characterized in that: The reaction process of the octocrylene derivative in step (1) is as follows: 。 5. The method for preparing a non-slip floor coating according to claim 3, characterized in that: The pre-modified nano-calcium carbonate in step (2) is prepared by uniformly mixing nano-calcium carbonate and anhydrous ethanol in a mass ratio of 1:(50-60), adding silane hydrolyzate in an amount of 8-10 times the mass of the nano-calcium carbonate, stirring at 50-60° C. and 300-500 r / min for 1-2 h, filtering, washing with anhydrous ethanol for 3-5 times, and drying at 50-60° C. under vacuum conditions for 7-8 h to obtain the pre-modified nano-calcium carbonate.

6. The method for preparing a non-slip floor coating according to claim 5, characterized in that: The silane hydrolyzate is prepared by uniformly mixing γ-aminopropyltriethoxysilane and deionized water in a mass ratio of 1:(20~30), adjusting the pH to 4~6 with a 1 mol / L oxalic acid aqueous solution, stirring at 10~30°C and 300~500r / min for 20~30min to prepare the silane hydrolyzate.

7. The method for preparing a non-slip floor coating according to claim 3, characterized in that: The pre-modified soybean oil in step (3) is prepared by uniformly mixing soybean oil, 3-mercapto-1,2-propanediol, azobisisobutyronitrile, and N,N-dimethylformamide in a mass ratio of 1:(0.6-0.8):(0.03-0.05):(8-10), stirring at 70-80°C and 300-500 r / min for 2-3 hours, and drying at 60-70°C under vacuum conditions for 7-8 hours to obtain the pre-modified soybean oil.

Citation Information

Patent Citations

  • Intumescent fire retardant compositions containing pentaerythritol cyclic diphosphates

    US4099975A

  • Materials having a fire-resistant coating containing a spirophosphonate

    WO2017080633A1